The ATPase VCP/p97 functions as a disaggregase against toxic Huntingtin‐exon1 aggregates. Issue 16 (13th August 2018) - Ghosh, Debasish Kumar; Roy, Ajit; Ranjan, Akash
Abstract : Intracellular protein aggregation is characterized by accumulation of misfolded proteins. Chaperones, degradation machineries, and quality‐control mechanisms counteract protein aggregation. In this study, we report that the ATPase valosin‐containing protein (VCP/p97) acts as a functional disaggregase that disassembles Huntingtin‐exon1 aggregates in vitro and in HeLa cells. The N‐terminal part of VCP (Cdc48_N domain) interacts with the N‐terminal 17‐amino acid region of Huntingtin‐exon1. We show that VCP has properties of a disaggregase, since it is capable of reducing preformed protein aggregates and displays increased ATPase activity in the presence of protein aggregates. However, VCP shows high divergence/disparity from other disaggregases. Taken together, our studies show the novel function of VCP/p97 as a disaggregase which detangles protein aggregates to probably channelize their degradation. Abstract :